Proteomic analysis of human blister fluids following envenomation by three snake species in India: differential markers for venom mechanisms of action - Macêdo, Jéssica Kale A. (2019)
Skin blistering as a result of snakebite envenomation is characteristic of some bites, however little is known regarding the mechanism of blister formation or the composition of the blister fluid. In order to investigate if blister fluid proteomes from humans suffering snakebite envenomation could provide insights on the pathophysiology of these skin alterations, blister fluid was collected from six patients upon presentation at a clinic in India bitten by three species of snakes, Daboia russelii (3), Hypnale hypnale (2), or Naja naja (1). Standard clinical data were recorded throughout the treatment. Approximately 805 proteins were identified in blister fluids using proteomic analyses. Informatics analyses of the proteomes identified the top biological response categories as: platelet degranulation, innate immune response, receptor-mediated endocytosis, complement activation, and blood coagulation. Hierarchical clustering did not show a clear segregation of patients’ proteomes being associated with the species of snake involved, suggesting that either the proteomic profiles described reflect a general response to venom-induced tissue damage or more patient data sets will be required to observe significant differences. Finally, it is of interest that venom proteins were also identified in the blister fluids suggesting that this fluid may serve as a reservoir of venom biologically active proteins/toxins, and as such, may indicate the clinical value of removing blister fluid to attenuate further tissue damage. The proteomic analysis of blister fluid collected from people suffering snakebite envenomation is a valuable tool to understand the pathophysiology of envenomation; to identify venom components; and to provide insights into new therapeutic options.